Upaya pelestarian pertanian oleh masyarakat dayak Meratus berbasis kearifan lokal manugal: Studi literatur - Sakinah, Rinrin; Surtikanti, Hertien Koosbandiah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The Dayak Meratus community is a community that is in harmony with nature because nature has provided a livelihood for them. One of the things that can be learned from the Dayak Meratus community is farming based on manugal local wisdom to preserve the environment, especially agriculture. The purpose of writing this review article is to review and describe the efforts to preserve agriculture by the Dayak Meratus community based on manugal local wisdom. The method used in writing this review article is library research, namely by collecting data by understanding and studying theories from various related literature. The results of the literature study state that the local wisdom of manugal is a farming process by making a hole using wood that is stuck into the ground, then filled with 5-7 rice seeds. The local wisdom of manugal is not just an ordinary farming tradition, but a tradition that contains socio-cultural values, the value of patience, and spiritual values between nature, culture and God. Thus, this local wisdom of manugal is expected to be a role model for utilizing natural resources properly and using them wisely for sustainable development so that every generation can experience the richness of nature, especially agricultural products.